International Handbook of Behavior Modification and Therapy 1990
DOI: 10.1007/978-1-4613-0523-1_29
|View full text |Cite
|
Sign up to set email alerts
|

Stuttering

Abstract: Over the past 5 years, there has been quite a dramatic decline in the number of data-based investigations or reports on or concerning stuttering therapy for adults or adolescents. After reviewing all English language journal publications that fit this category, this writer found that in 1973-1977 there were 57 reports, in 1978-1982 there were 50 reports, but in 1983-1987 (and including half of 1988) there were only 25 reports. A. S. Bellack et al. (eds.), International Handbook of Behavior Modification and Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 274 publications
0
6
0
Order By: Relevance
“…This disorder provides a fascinating disease model of speech production not only because of its high prevalence in the population (approximately 1%) but because of its marked gender ratio (3:1 ratio of men:women), probable genetic basis, and responsiveness to environmental stimuli [Bloodstein, 1995]. There is a high rate of recovery in children, but stuttering that persists into adolescence or adulthood is much more resistant to recovery [Ingham, 2001a]. Although the core pathology underlying developmental stuttering remains poorly understood, much research has effectively excluded the peripheral vocal system as the cause of the disorder and has instead placed the focus on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disorder provides a fascinating disease model of speech production not only because of its high prevalence in the population (approximately 1%) but because of its marked gender ratio (3:1 ratio of men:women), probable genetic basis, and responsiveness to environmental stimuli [Bloodstein, 1995]. There is a high rate of recovery in children, but stuttering that persists into adolescence or adulthood is much more resistant to recovery [Ingham, 2001a]. Although the core pathology underlying developmental stuttering remains poorly understood, much research has effectively excluded the peripheral vocal system as the cause of the disorder and has instead placed the focus on the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, stuttering is distinct from other speechmotor disorders in being more or less specific for speech, in comparison to syndromes such as dysarthria that tend to be part of generalized syndromes affecting motor control throughout much of the body [Kent, 2000]. The cause of chronic developmental stuttering remains unknown, resulting in a plethora of competing theories [Ingham, 2001a].…”
Section: Introductionmentioning
confidence: 99%
“…Recovery is generally considered to be associated with a reduction in the frequency and severity of stuttering (e.g. Ingham, 1984; Starkweather, 1993; Yairi, 1993, 1996). To establish any such reduction, additional speech samples need to be obtained and analyzed using the standardized measurement instrument again (Riley, 1994) when the child passes age 12 by which time recovery will have taken place if it was going to happen at all (Andrews & Harris, 1964).…”
mentioning
confidence: 99%
“…An analysis of the treatment results of several hundred child clients which have been published in the literature revealed that the three procedures above have been shown to reduce stuttering from an average 10% stuttering to less than an average 1% stuttering or percent syllables stuttered (%SS) with normal speaking rates of around 200 syllables per minute (SPM), both well within the range of normally fluent speech of those who do not stutter (Ryan, 2001, p. 42). Further, clear, replicable descriptions in manuals (e.g., Ingham, 1981), or books (e.g., Ryan, 2001d) of these procedures can be found in several places including the internet (e.g., the Lidcombe Program, www.fhs.usyd.edu.au/asrc/). Published efficiency data suggest an average of 10 to 20 hours of treatment.…”
Section: Treatment Efficacy Results Datamentioning
confidence: 99%
“…The third of these programs is prolonged speech (PS) (“IIIwaaantoogooo”)” which is gradually speeded up until it sounds natural at normal rates of speaking (“I want to go.”) (e.g., Ingham, 1981, 1984; Kully & Boberg, 1991; Ryan, 1971, 1974, 2001d, pp. 93–111, Ryan & Ryan, 1983, 1995).…”
Section: Establishment Programsmentioning
confidence: 99%